Puasa dan Kesehatan Fisik (Kajian Medis) Mata Kuliah Interdisipliner Pendidikan Islam Berbasis Al- Quran dan Hadits - Latifatul Azizah; Syamsurizal Yazid (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Abstract, Fasting in Islam is not only an act of worship that brings one closer to Allah, but also offers physical and mental health benefits. In addition to increasing piety, fasting helps discipline oneself and supports the body's detoxification process. The biological processes that occur during fasting, such as rest for the digestive system and the use of energy reserves, demonstrate Allah's wisdom. Fasting also prevents diseases caused by overeating, such as hypertension, diabetes, and heart problems. Medical research reveals that moderate eating patterns and regular fasting improve overall health. Fasting, such as during Ramadan, also boosts metabolism, organ health, and psychological well-being by regulating emotions and behavior. Various types of fasting, both obligatory and voluntary, have different health impacts, and studies support the benefits of fasting in reducing inflammation, regulating blood glucose levels, and enhancing overall quality of life.